2021
DOI: 10.1111/aogs.14138
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of spontaneous preterm birth by cervical length in the first trimester of pregnancy: Comparison of two measurement methods

Abstract: Introduction Our objectives were to compare the single‐line and two‐line methods of cervical length measurement in the first trimester of pregnancy and to evaluate the potential value of the first trimester cervical length measured by the two methods in predicting spontaneous preterm birth. Material and methods This was a prospective study in singleton pregnancies at 11+0 to 13+6 weeks of gestation. Cervical length was measured by two methods: (i) a linear distance between the two ends of the glandular area ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…[12] There is, however, still controversy regarding the role of CL measurement in the first trimester in the prediction of PTB. [11,[13][14][15] Furthermore, a history of previous PTB, which is known to be an independent predictor of PTB [16], has been found to increase PPROM prediction if combined with a CL measurement in the second trimester. [17] Cervical surgery has been shown to predispose women to PTB, and this risk may be proportional to the amount of tissue removed from the cervix during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…[12] There is, however, still controversy regarding the role of CL measurement in the first trimester in the prediction of PTB. [11,[13][14][15] Furthermore, a history of previous PTB, which is known to be an independent predictor of PTB [16], has been found to increase PPROM prediction if combined with a CL measurement in the second trimester. [17] Cervical surgery has been shown to predispose women to PTB, and this risk may be proportional to the amount of tissue removed from the cervix during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…However, the screening performance of the first-trimester combined model that includes maternal risk factors and biomarkers of placental function (PAPP-A and PlGF) is suboptimal. Several groups have shown that first-trimester cervical length may be a useful screening tool for sPTB [36][37][38][39][40] . Future studies should aim to evaluate whether addition of cervical length and other biomarkers will improve the screening performance of the combined model.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical length assessment in the second trimester through transvaginal ultrasound assessment is a strong predictor for spontaneous preterm birth. Cervical length ≤ 25 mm at 22 + 0 to 24 + 6 weeks of gestation has been associated with 37.3% sensitivity, 92.2% speci city, 17.8% positive predictive value, and 97.0% negative predictive value for the prediction of spontaneous preterm birth at < 35 weeks of gestation (10). The Anterior uterocervical angle is de ned as the angle between the cervix and the anterior uterine wall; this angle can be measured by ultrasound and its width can be of great value in predicting preterm birth.…”
Section: Introductionmentioning
confidence: 99%